Double Output Positive Conversion Path Re-Lift Luo Converter Performance with Intelligent Control Strategies - D. Thaniga, Dr. S. Padma, Dr. R. Kannan (South Eastern European Journal of Public Health, 2025)
This study investigates double-output DC-DC Luo converters as a cost-effective, high-power-density solution for generating positive and negative output voltages from a single positive input source, addressing the increasing demand for such converters in modern electronics. The research focuses on the development and comparison of control strategies for a Double Output Positive Conversion Path Re-lift (DOPCPRL) Luo Converter. Specifically, Proportional-Integral and fuzzy logic controllers are designed and implemented to regulate the output voltage under varying input voltage and load conditions. Performance evaluation through simulation demonstrates the superior performance of the fuzzy logic controller and neural network controllers compared to the traditional PI controller, highlighting its effectiveness in maintaining stable and accurate output voltage regulation. The results underscore the potential of intelligent control techniques for enhancing the performance of Luo converters in demanding applications.